2023
DOI: 10.1088/1748-9326/acdc3d
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur isotopes quantify the impact of anthropogenic activities on industrial-era Arctic sulfate in a Greenland ice core

Abstract: Anthropogenic sulfate aerosols are estimated to have offset sixty percent of greenhouse-gas-induced warming in the Arctic, a region warming four times faster than the rest of the world. However, sulfate radiative forcing estimates remain uncertain because the relative contributions from anthropogenic versus natural sources to total sulfate aerosols are unknown. Here we measure sulfur isotopes of sulfate in a Summit, Greenland ice core from 1850 to 2006 CE to quantify the contribution of anthropogenic sulfur em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…δ 34 S emission is assumed to be the same as primary sulfate (δ 34 S primary = +4.7(±0.6)‰) since sulfur isotope fractionation of fuel oil during high-temperature combustion is expected to be minimal . This is consistent with previous studies that assume primary sulfate from combustion retains the δ 34 S(SO 4 2– ) signature of the sulfur source. We assume that Fairbanks is a closed system, where long-range transport of biogenic and volcanic sulfur can be neglected. This assumption is further supported by prior literature showing that the pollution layer is often confined lower than 20 meters in Fairbanks with the highest PM 2.5 concentrations below 3 meters. ,,, On-road mobile sampling performed by Robinson et al (2023) found the lowest PM 2.5 concentrations at the top of hills and asserted that residential neighborhoods were unequivocally the dominant PM source. δ 34 S false( normalSO 4 2 false) false( false) = f primary × δ 34 S primary + false( 1 normalf normalprimary false) × false( δ 34 normalS normalemission ( f H 2 O 2 · ε H 2 O 2 + f O 3 · ε …”
Section: Methodsmentioning
confidence: 54%
“…δ 34 S emission is assumed to be the same as primary sulfate (δ 34 S primary = +4.7(±0.6)‰) since sulfur isotope fractionation of fuel oil during high-temperature combustion is expected to be minimal . This is consistent with previous studies that assume primary sulfate from combustion retains the δ 34 S(SO 4 2– ) signature of the sulfur source. We assume that Fairbanks is a closed system, where long-range transport of biogenic and volcanic sulfur can be neglected. This assumption is further supported by prior literature showing that the pollution layer is often confined lower than 20 meters in Fairbanks with the highest PM 2.5 concentrations below 3 meters. ,,, On-road mobile sampling performed by Robinson et al (2023) found the lowest PM 2.5 concentrations at the top of hills and asserted that residential neighborhoods were unequivocally the dominant PM source. δ 34 S false( normalSO 4 2 false) false( false) = f primary × δ 34 S primary + false( 1 normalf normalprimary false) × false( δ 34 normalS normalemission ( f H 2 O 2 · ε H 2 O 2 + f O 3 · ε …”
Section: Methodsmentioning
confidence: 54%
“…We measure concentrations of MSA and sulfate (SO 4 2– ) and sulfur isotopes (δ 34 S) of sulfate in ice core samples from 1200 to 2006 CE ( Materials and Methods ). Sulfur isotopes are used to estimate the relative contribution from each of the main sources of Arctic sulfate: DMS, volcanic, and anthropogenic emissions ( 30 35 ). The influence of sea salt is subtracted from the sulfate concentration and sulfur isotope measurements ( Materials and Methods ).…”
Section: Resultsmentioning
confidence: 99%
“…where f anthro is the fraction of anthropogenic sulfate in the sample and δ 34 S anthro is the anthropogenic sulfur isotopic source signature, which is estimated to be +2.9 ± 0.3‰ [ SI Appendix, Supplementary Text S3 , ( 35 )]. We assume that source signatures (δ 34 S bio , δ 34 S volc , and δ 34 S anthro ) are relatively constant over time ( SI Appendix, Supplementary Text S3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations